Strategic Analysis of PT Griyacom : Enhancing Competitiveness in a Dynamic Market - Keumala Hayati; Raden Ayu Nabila Rafa Arfiansyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Indonesia's computer retail industry is becoming increasingly competitive due to rapid technological advancements and evolving consumer preferences. PT Griyacom, a computer retail company in Bandar Lampung, faces challenges in sustaining its competitiveness amid these market dynamics. This study examines the business strategies adopted by PT Griyacom to enhance its competitive advantage using a qualitative approach with a case study method. Data was gathered through in-depth interviews with company management, direct observations, and document analysis, while data analysis followed the Miles and Huberman model, encompassing data reduction, data presentation, and conclusion drawing. The findings indicate that PT Griyacom has implemented various business strategies, including improving customer service, expanding product diversification, and utilizing digital marketing. However, the company still faces challenges such as intense price competition and the need for greater technological innovation. Based on these findings, this study offers strategic recommendations for PT Griyacom to strengthen its market position by optimizing digital marketing efforts, enhancing operational efficiency, and reinforcing product differentiation.